Effects of Neck-Arm Restraint Suspension of Beef Carcasses on Meat Quality and Proteome of Different Muscles During Post-mortem Aging - Cai, Wentao; Wen, Kaixin; Che, Leijie; Zhang, Haijun; Zhang, Yang; Li, Junya; Li, Haipeng (Frontiers in Nutrition, 2021)
Beef quality is the first deciding factor for consumers to consider before purchasing. The aim of this study was to evaluate the effects of suspension and aging time on beef quality. We compared the differences in pH, drip loss, cooking loss, color, shear force, myofibril fragmentation index (MFI) and electron microscope of three muscle tissues between Achilles tendon (AT) and neck-arm restraint (NR) suspensions during seven aging periods (day 0, 1, 2, 3, 7, 14 and 21) after slaughter using the carcasses of six Xinjiang brown cattle. We found that NR suspension could significantly increase water loss rate and MFI, as well as reduce shear force compared to AT suspension. The muscle fiber structure with NR suspension was more severely damaged. The proteomics of longissimus dorsi were checked for the post-mortem day 1, 7 and 14. We detected 50, 26, and 29 differential expressed proteins (DEPs) between NR and AT suspension at post-mortem day 1, 7 and 14, respectively. These proteins were involved in metabolic and muscle structure associated pathways, and contributed to a comprehensive understanding of suspension-dependent meat quality regulation by proteins in beef cattle. To conclude, NR suspension can accelerate the aging time of beef carcasses, which will reduce the cost of carcass suspension and bring more benefits in beef industry.